An Empirical Investigation into the Role of Technology Gap in the Trade Relations of the EU Member States - Tomasz Brodzicki; Jakub Kwiatkowski (Entrepreneurial Business and Economics Review, 2018)
Objective: The objective of this article is an empirical analysis of the role of technology gap in explaining the intensity of trade relations of the EU28 Member States over the period 1995-2015.